2016
DOI: 10.3109/13561820.2016.1159186
|View full text |Cite
|
Sign up to set email alerts
|

Twelve possible strategies for enhancing interprofessional socialisation in higher education: Findings from an interpretive phenomenological study

Abstract: The aim of this study was to investigate the interprofessional socialisation experiences of health professional educators (HPEs) across five health science faculties in Perth, Australia. Evidence supported the importance of educators teaching and learning together, although there was minimal evidence with regard to the type of support HPEs received or required in order to socialise interprofessionally within higher education. Interview participants comprised 26 HPEs from various health-related professions acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The health professional educators in this study indicated that there was a lack of socialization preventing them from integrating to their faculty roles and further delaying collaborative work (Stanley et al, 2016). Participants offered a total of 100 suggestions for improving IS leading to 12 formal and informal strategies.…”
Section: Strategies For Is Strategies To Enhance the Is Experiences mentioning
confidence: 98%
See 4 more Smart Citations
“…The health professional educators in this study indicated that there was a lack of socialization preventing them from integrating to their faculty roles and further delaying collaborative work (Stanley et al, 2016). Participants offered a total of 100 suggestions for improving IS leading to 12 formal and informal strategies.…”
Section: Strategies For Is Strategies To Enhance the Is Experiences mentioning
confidence: 98%
“…educators have been explored. An interpretive phenomenological study included 26 health professional educators to discover the phenomena of IS (Stanley, Dixon, Warner, & Stanley, 2016). This study utilized purposeful sampling to ensure representation of professions.…”
Section: Strategies For Is Strategies To Enhance the Is Experiences mentioning
confidence: 99%
See 3 more Smart Citations